Synthesis, Spectral and Biological Studies of Metal Complexes with Heterocyclic Ligand Derived from Thaizolylazo Dye - Khalid J. Al-Adilee (Journal of Global Pharma Technology, 2018)
Metal (II) complexes have been synthesized with new azo dye ligand 2-[2–(4, 5-dimethyl thiazolyl) azo]-4-benzyl phenol (DMeTABP=HL) derived from coupling reaction between 4, 5–di methy thiazaolylazonium chloride and 4 – benzyl phenol in alkaline alcoholic solution. Azo dye ligand and metal complexes have been characterized by elemental analysis (C.H.N.S), 1H-NMR , mass, Electronic, IR , XRD spectral data , SEM ,thermal analysis (TGA,DSC and DTG) , magnetic susceptibility , metal contents and molar conductance .The elemental analysis of the metal chelate complexes confirms the stoichiometry of the type [ M(L)2 ] , where M =Ni(II) , Cu(II) , Zn(II) and [M(L)2]Cl and where M = Co (III) and L = azo dye ligand. The spectra and analytical data indicated that the ligand (DMeTABP) behaves as tridentate chelating agent with l: 2 [M: L] complexes and octahedral geometry. Conductance measurement suggests the l:l electrolytic nature of Co(III) complexes but non- electrolytic nature of the rest metal complexes. The biological activity of azo dye ligand and its metal complexes against the pathogenic activities was tested against the sensitive organisms Escherichia coli (gram negative), streptococcus, staphylococcus (gram positive) as antibacterial and Alternaria spp as antifungal. The activity data show that the metal complexes were of higher antibacterial and antifungals activity than the free ligand. The results are discussed. The biological activity also conducted cells viability and cytotoxicity assay on Cu (II) and Zn (II) _complex by using the lines of cancerous liver cells of the type HePG2 and compared with line of the ordinary cellsKeywords: Thiazolyl azo ligand, Metal complexes Characterization, Antibacterial, Antifungal and anticancerious.